If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9-n=-2n
We move all terms to the left:
-9-n-(-2n)=0
We add all the numbers together, and all the variables
-1n-(-2n)-9=0
We get rid of parentheses
-1n+2n-9=0
We add all the numbers together, and all the variables
n-9=0
We move all terms containing n to the left, all other terms to the right
n=9
| 54=0.9r | | 6y-3=5y-1 | | 64+49+m=18 | | x+5(6x+3)=10 | | 4p-(p-5)=8+3(2p-2) | | -6h=-8-8h | | 0.5x=0.2+0.1x+0.1 | | 2r+7=r | | 2v=27-v | | x—60=20 | | 13=19-c | | 3(x+5)-(x-1)=4(3x+8 | | 6=4-5b | | 5=1+1b | | 12h=9h+82 | | -11-2-2p+10p=1+8p-4 | | A(t)=-t(2)+6t+18 | | -4-8d=17 | | 3a+5a-12=84 | | 3.75=1.5^x | | 2x+2=—52 | | 30.5=7z-3.5z | | x-25=2x-4 | | 30.5=7-z-3.5z | | -7p-3(4p+17)=-124 | | 8m-2(3m-4)=-10 | | 1/8f+3=0 | | 2/5m-3=1 | | 10p=10.36 | | s/3-8=12 | | -4(2x-3)=15-8x | | s-9.03=5.07 |